Systemic Lupus Erythematosus Presenting as Acute Lupus Pneumonitis during Pregnancy - Marlene Marte Furment; Suyansh Sharma; Sangeetha Pabolu (Case Reports in Rheumatology)
Introduction. This is a case of new-onset systemic lupus erythematosus (SLE) manifesting as acute pneumonitis during pregnancy. No prior reports have documented pneumonitis as the presenting manifestation of SLE in pregnant women. Case Presentation. A 23-year-old pregnant female presented with high-grade fever, cough, arthralgias, and respiratory failure. Infectious workup was negative. She was positive for ANA, anti-dsDNA, anti-SSA, hypocomplementemia, and pulmonary infiltrates, supporting the diagnosis of SLE and pneumonitis. The patient received methylprednisolone achieving adequate clinical and serological response. Conclusion. When SLE patients present with fever, cough, and respiratory failure, pulmonary infiltrates should raise the suspicion of pneumonitis in the absence of infection and hemorrhage. Even though acute lupus pneumonitis (ALP) is rare and seen only in 2% of SLE patients, a high index of suspicion aids in prompt diagnosis of this life-threatening condition. Also, positive anti-SSA antibodies may be associated with lupus pneumonitis.